STUDENT EFL PERSPECTIVE TOWARDS EFFECTIVENESS EBOOKS AND PRINTED BOOKS IN A PANDEMIC SITUATION FOR INCREASING READING COMPREHENSION AT UNIVERSITY SINGAPERBANGSA KARAWANG - Seto Kurniadi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
The present study reports students’ responses on the usage of e-books as well as its effectiveness following their experience. This study also examines the students’ preference and experience for printed books and e-books. The method of this research is qualitative method. The data was collected through observation, interview, and documentation. Qualitative findings show that: (1) All of the students had an interest in using e-book in pandemic situation; (2) the use of e-book in in pandemic situation made students independent and active in reading comprehension; (3) e-book engaged them in reading comprehension rather than printed book; (4) e-book motivated students in reading comprehension. The findings of this study may be useful to other researchers who are interested in EFL teaching innovation or teachers who seek effective reading teaching method.